Aplikasi Pewarnaan Graf untuk Menentukan Jadwal Ujian Skripsi di Prodi Pendidikan Matematika ITSNU Pasuruan - Lestari, Isnawati Lujeng; Umilasari, Reni (Center of Education Journal (CEJou), 2022)
In 2022, Matematics Education of ITSNU Pasuruan will conduct a Thesis examination for the first batch of student. In order to be more effective and there is no overlap in the implementation of the thesis exam, proper and efficient techniques are needed in solving problems in the preparation of the thesis exam schedule. One of the the techniques that can be used for the preparation of the thesis exam schedule is by applying graph coloring with the main -sequence algorithm. The reseach method used in this research is literature study and data collection. The algorthm can be applied in preparing the thesis exam schedule at the Matematics Education ITSNU Pasuruan. The result of this study obtained seven test schedule that can be used so that there are no clashes between the thesis exam schedule with the same supervisior. Suggestiob for the further research to improve in terms of schedule accurary, space, time and other variable so that the schedule obtained is more efficent and effective.